Tamara Grigorieva as Action, in Les presages, Covent Garden Russian Ballet, Australian tour, His Majesty's Theatre, Melbourne, April, 1939 (2) - Hall, Hugh P.; Massine, Leonide, 1896-1979.; Masson, André, 1896-1987.; Shervashidze, Aleksandr, 1867-1968. (1939)
One of a collection of photographs taken by Hugh P. Hall of 28 ballet productions performed by the Covent Garden Russian Ballet (toured Australia 1938-1939) and the Original Ballet Russe (toured Australia 1939-1940). These are the second and third of the three Ballets Russes companies which toured Australasia between 1936 and 1940. The photographs were taken from the auditorium during a live performance in His Majesty's Theatre, Melbourne and mounted on cardboard for display purposes. For conservation and storage, the photographs have been demounted. The original arrangement of the photographs has been recorded, and details are available from the Pictures Branch of the National Library.
Inscription: "L4".
From: Les presages (Destiny) : choreographic symphony / by Leonide Massine ; music by Peter Ilich Tchaikovsky from his Fifth symphony.
Part of the collection: Hugh P. Hall collection of photographs, 1938-1940.
Choreography by Leonide Massine ; scenery and costumes by Andre Masson ; scenery executed by Prince A. Schervachidze.
Also available online
Keywords: Covent Garden Russian Ballet -- Performances -- Photographs; His Majesty's Theatre (Melbourne, Vic.) -- Photographs; Presages (Choreographic work) -- Photographs; Ballet dancers -- Photographs; Ballet -- Australia -- Photographs; Ballets Russes in Australia